2013
DOI: 10.1175/jhm-d-12-067.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the CLM4 Lake Model at a Large and Shallow Freshwater Lake*

Abstract: Models of lake physical processes provide the lower flux boundary conditions for numerical predictions of weather and climate in lake basins. So far, there have been few studies on evaluating lake model performance at the diurnal time scale and against flux observations. The goal of this paper is to evaluate the National Center for Atmospheric Research Community Land Model version 4–Lake, Ice, Snow and Sediment Simulator using the eddy covariance and water temperature data obtained at a subtropical freshwater … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 47 publications
3
56
0
Order By: Relevance
“…The data collected at Lake Taihu have been used to improve the lake model in NCAR's Community Land Model (CLM) system. In contrast, we found that for Lake Taihu the diffusivity should be adjusted downward by 92% in order for the model to reproduce successfully the observed diurnal variations in the lake surface temperature (Deng et al 2013). Tests of the model for deep lakes reveal that the eddy thermal diffusivity given by the model is 1-2 orders of magnitude too low (Martynov et al 2010;Subin et al 2012).…”
Section: Research Design Eddy Covariancementioning
confidence: 83%
See 1 more Smart Citation
“…The data collected at Lake Taihu have been used to improve the lake model in NCAR's Community Land Model (CLM) system. In contrast, we found that for Lake Taihu the diffusivity should be adjusted downward by 92% in order for the model to reproduce successfully the observed diurnal variations in the lake surface temperature (Deng et al 2013). Tests of the model for deep lakes reveal that the eddy thermal diffusivity given by the model is 1-2 orders of magnitude too low (Martynov et al 2010;Subin et al 2012).…”
Section: Research Design Eddy Covariancementioning
confidence: 83%
“…To date, some progress has been made toward answering the first science question, using data from a subset of the eddy flux sites (Deng et al 2013;Xiao et al 2013;Wang et al 2014). To date, some progress has been made toward answering the first science question, using data from a subset of the eddy flux sites (Deng et al 2013;Xiao et al 2013;Wang et al 2014).…”
Section: Motivation and Science Questionsmentioning
confidence: 99%
“…According to the Priestley-Taylor model (Priestley and Taylor 1972), open water evaporation is controlled by the available energy and temperature and is independent of wind speed. Parameter analysis with the CLM4-LISSS lake model indicates that the surface temperature of Lake Taihu is insensitive to wind (Deng et al 2013). In the present study, increasing the MERRA wind speed by 10 % changed the mean evaporation rate only slightly, by 0.4 % to 981 mm from the original mean of 977 mm.…”
Section: Discussionmentioning
confidence: 99%
“…The main forcing variables are net shortwave radiation flux, downward longwave radiation flux, wind speed at the 10-m height, and specific humidity and air temperature at the 2-m height. Recently, our group (Deng et al 2013) evaluated the model against the eddy covariance observations at Lake Taihu. We found that the model does a good job simulating the eddy fluxes and the water temperature after an adjustment has been made to the water thermal diffusivity parameterization.…”
Section: The Lake Land-surface Modelmentioning
confidence: 99%
See 1 more Smart Citation